Contextualizing the standard maternal continuum of care in Pakistan: an application of revised recommendation of the World Health Organization - Rahaman, Margubur; Roy, Avijit; Chouhan, Pradip; Malik, Najma Iqbal; Bashir, Shamshad; Ahmed, Farooq; Tang, Kun (Frontiers in Public Health, 2024)
Objective: This study utilizes recent nationally representative data to contextualize the standard maternal continuum of care (SMCoC) in Pakistan. The revised SMCoC framework encompasses at least eight antenatal care visits, skilled birth attendants during delivery, and postnatal care within 48 hours of childbirth. Methods: The study used a sample of 3,887 ever-married women aged 15-49 from the latest Pakistan Demographic and Health Survey (PDHS) conducted in 2017-18. Several statistical methods were employed: descriptive statistics, bivariate, multilevel logistic regression models, and Fairlie decomposition analysis. Results: Only 12% of women had accessed full SMCoC services in Pakistan. Education and the wealth quintile emerged as pivotal factors influencing the Standard Maternal Continuum of care in Pakistan 2This is a provisional file, not the final typeset article utilization of SMCoC. The likelihood of full SMCC utilization was more likely among higher educated women (OR: 3.37; 95% CI: 2.16-5.25) and those belonging to the wealthiest household wealth quintile (OR: 4.95; 95% CI: 2.33-5.51). Media exposure, autonomy, healthcare accessibility, residence, and region were also identified as significant predictors of SMCoC utilization among women.In conclusion, while most women did not utilize full SMCoC services in Pakistan, the pattern is substantially varied by background characteristics. Education, wealth quintile, mass media exposure, and autonomy were significant factors, along with geographical aspects such as healthcare accessibility and region. The study underscores the need for a multifaceted approach to ensure equitable access to full SMCoC services for women in Pakistan, addressing individual, socioeconomic, and geographical factors.